Improving health and social systems for all children in LMICs: structural innovations to deliver high-quality services. Issue 10337 (7th May 2022) - Kruk, Margaret E; Lewis, Todd P; Arsenault, Catherine; Bhutta, Zulfiqar A; Irimu, Grace; Jeong, Joshua; Lassi, Zohra S; Sawyer, Susan M; Vaivada, Tyler; Waiswa, Peter; Yousafzai, Aisha K
Summary: Despite health gains over the past 30 years, children and adolescents are not reaching their health potential in many low-income and middle-income countries (LMICs). In addition to health systems, social systems, such as schools, communities, families, and digital platforms, can be used to promote health. We did a targeted literature review of how well health and social systems are meeting the needs of children in LMICs using the framework of The Lancet Global Health Commission on high-quality health systems and we reviewed evidence for structural reforms in health and social sectors. We found that quality of services for children is substandard across both health and social systems. Health systems have deficits in care competence (eg, diagnosis and management), system competence (eg, timeliness, continuity, and referral), user experience (eg, respect and usability), service provision for common and serious conditions (eg, cancer, trauma, and mental health), and service offerings for adolescents. Education and social services for child health are limited by low funding and poor coordination with other sectors. Structural reforms are more likely to improve service quality substantially and at scale than are micro-level efforts. Promising approaches include governing for quality (eg, leadership, expert management, and learning systems), redesigning service delivery to maximise outcomes, and empowering families to better care for children and to demand quality care from health and social systems. Additional research is needed on health needs across the life course, health system performance for children and families, and large-scale evaluation of promising health and social programmes.